Destination sectors and originating economies of Nigeria's private foreign assets and liabilities in 2012 - Sani I. Doguwa; Mohammed M. Tumala; Olufemi I. Ajibola (CBN Journal of Applied Statistics, 2014)
The 2013 survey of foreign assets and liabilities of enterprises in Nigeria was conducted to determine destination sectors of foreign private capital flows and economies where such investments originate. The survey covered 649 large establishments in Nigeria with 87.4 per cent response rate. The cross border transactions/investments of the respondents during 2011 and 2012 indicate total foreign claims on the Nigerian economy as at end 2012 rising to N16, 790.78 billion from N13, 647.19 billion recorded in 2011. Of this total, 98.1per cent came in the form of direct investments, while portfolio investments and other capital flows accounted for 1.1 and 0.8 per cent, respectively. About 39 per cent of the total inflow originated from Europe, while 16.7 per cent and 16.3 per cent originated from the Middle East and North America, respectively. A breakdown in terms of destination sectors revealed that extractive industries sector attracted 40.5 per cent and is followed by manufacturing, which received 27.7 per cent. Total stock of outward investment as at end 2012 was N235.94 billion as against N208.44 billion recorded in 2011. In 2012, outward direct investment dominated with 76.5 per cent of the total, while European countries were the preferred investment destination for Nigerian enterprises receiving 57.4 per cent of the total outflow, followed by Africa (27.2 per cent).
Keywords: 330